Family support and the perception of chronic pain in patients with cancer - Setyati, Dian; Setyowati, Wahyu Endang; Rochmawati, Dwi Heppy (JOURNAL OF Mental Health Concerns, 2026)
Background: Chronic pain is a common symptom among cancer patients and significantly affects quality of life across physical, psychological, and social domains. Pain perception is influenced not only by biological factors such as disease progression and treatment, but also by psychosocial factors, particularly family support. Family support plays an important role in enhancing coping mechanisms, reducing stress, and shaping patients’ responses to pain. However, empirical evidence on the relationship between family support and chronic pain perception among cancer patients in Indonesia remains limited. Purpose: To examine the relationship between family support and chronic pain perception among cancer patients. Method: A quantitative non-experimental study with a cross-sectional design was conducted involving 30 hospitalized cancer patients selected through total sampling. Family support was assessed using the family subscale of the Multidimensional Scale of Perceived Social Support (MSPSS), while chronic pain perception was measured using the Brief Pain Inventory (BPI) Short Form. Results: Data analysis using Somers’ d test revealed a strong and statistically significant negative association between family support and chronic pain perception (r = −0.800; p<0.05). Conclusion: These findings underscore the importance of integrating family support into family-centered approaches for cancer pain management. Keywords: Cancer Patients; Chronic Pain Perception; Family-Centered Care; Family Support; Nursing.